Stress hyperglycemia ratio and neutrophil to lymphocyte ratio are reliable predictors of new-onset atrial fibrillation in patients with acute myocardial infarction - Pan, Lifei; Li, Zhitong; Li, Chenglin; Dong, Xiaopeng; Hidru, Tesfaldet H.; Liu, Fei; Xia, Yunlong; Yang, Xiaolei; Zhong, Lei; Liu, Ying (Frontiers in Cardiovascular Medicine, 2022)
Background: The occurrence of new-onset atrial fibrillation (NOAF) post-acute myocardial infarction (AMI) is associated with worse outcomes. In this study, we sought to assess the predictive effect of stress hyperglycemia ratio (SHR) and neutrophil to lymphocyte ratio (NLR) to predict NOAF in patients with AMI. Method: We recruited 3194 individuals with AMI but free of atrial fibrillation (AF). AMI cases were stratified into groups according to SHR and NLR quartiles and were further categorized based on diabetes status. High SHR and high NLR were defined as the highest quartile of SHR and NLR. A nomogram incorporating risk factors for NOAF was constructed using multivariate logistic regression analyses. The performance of the novel nomogram was tested for predictive performance, agreement between the actual and predicted probability, and clinical utility using area under the curve (AUC), bootstrapped calibration curves, and decision curve analysis, respectively. Result: A total of 245 (7.67%) patients developed NOAF post-AMI. The NOAF cases had higher values of SHR and NLR than non-NOAF patients after AMI regardless of diabetes status. After adjusting for potential confounders, high SHR and NLR were independently associated with NOAF post-AMI. Moreover, the novel nomogram incorporating high NLR and high SHR for NOAF risk estimation in patients with AMI showed satisfactory performance assessed by the AUC, calibration curves, decision curve analysis, and survival curves. Conclusion: SHR and NLR were independently associated with NOAF in AMI patients. The constructed novel nomogram that incorporates SHR and NLR might assist in NOAF risk stratification post-AMI.